What ‘Postdigital’ Means to Us: Roundtable with Members of the Centre for Postdigital Cultures - Janneke Adema; Sylvester Arnab; Adrienne Evans; Mel Jordan; Petros Lameras; Marcus Maloney; Kevin Walker (Anglica. An International Journal of English Studies)
Facilitated by the sixth author, this roundtable was conducted on 24 January 2024, at Coventry University. It brings together members of the Centre for Postdigital Cultures, Coventry University, from the centre’s five core research strands: Postpublishing; Postdigital Intimacies; ArtSpaceCity; Ludic Design; and AI and Algorithmic Cultures. Here we explore the multifaceted and interdisciplinary meaning to us of the concept of the ‘postdigital’ and unpack the salient characteristics that make it an important concept in future practice-research-theory.